2021
DOI: 10.1016/j.jbc.2021.100963
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 4 contributes to Alzheimer’s disease–like defects in a mouse model and is increased in sporadic Alzheimer’s disease brains

Abstract: Please cite this article as: RRH: DPP4 contributes to Alzheimer's disease This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…DPP4 removes X-Pro/Ala N-terminal dipeptides (where X is any amino acid) from substrates of <100 residues, including glucagon-like peptide-1 and amyloid-β peptides ( 31 , 34 ), as long as the third residue is not Pro (i.e., X-Pro/Ala↓ . Internal cleavage of PrP C , a protein of >200 residues, is not in line with the canonical function of DPP4, but certain DPP4 inhibitors target FAP as well; indeed, the most effective compounds in our study, linagliptin and talabostat, reportedly inhibit FAP with IC 50 s of 370 nM and 70 nM, respectively, which are closer to the values we observed than the relatively consistent low-nanomolar potencies that the DPP4 inhibitors display toward DPP4 itself ( 34 , 35 ). Moreover, in addition to its DPP4-like exopeptidase activity, FAP acts as an endopeptidase favoring the sequence Gly–Pro↓ ( 30 , 36 , 37 )—motifs present in multiple copies within the mutated S3 PrP OR domain (Gly–Gly–Gly/Ser→Gly–Pro–Gly/Ser).…”
Section: Resultsmentioning
confidence: 99%
“…DPP4 removes X-Pro/Ala N-terminal dipeptides (where X is any amino acid) from substrates of <100 residues, including glucagon-like peptide-1 and amyloid-β peptides ( 31 , 34 ), as long as the third residue is not Pro (i.e., X-Pro/Ala↓ . Internal cleavage of PrP C , a protein of >200 residues, is not in line with the canonical function of DPP4, but certain DPP4 inhibitors target FAP as well; indeed, the most effective compounds in our study, linagliptin and talabostat, reportedly inhibit FAP with IC 50 s of 370 nM and 70 nM, respectively, which are closer to the values we observed than the relatively consistent low-nanomolar potencies that the DPP4 inhibitors display toward DPP4 itself ( 34 , 35 ). Moreover, in addition to its DPP4-like exopeptidase activity, FAP acts as an endopeptidase favoring the sequence Gly–Pro↓ ( 30 , 36 , 37 )—motifs present in multiple copies within the mutated S3 PrP OR domain (Gly–Gly–Gly/Ser→Gly–Pro–Gly/Ser).…”
Section: Resultsmentioning
confidence: 99%
“…The different classes differ, however, in their distributions of mutational effects, with substitutions and insertions in the N-terminus more likely to impair rather than enhance aggregation but single and multi-AA deletions more likely to enhance rather than impair it. N-terminal truncations of Aβ are particularly likely to accelerate nucleation, raising the intriguing possibility that increased production of N-terminally truncated forms of Aβ triggered by environmental exposures, pathogens or genetics might be an important cause of familial and sporadic AD 50 .
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Antonyan et al [ 23 ] have demonstrated that purified DPP4 acts together with glutaminyl cyclase (QC) activity to generate Aβ pE3-40/42 in vitro by MALDI-TOF mass spectrometry. Valverde et al [ 26 ] added convincing evidence that human recombinant DPP4 is the rate-limiting enzyme liberating Aβ 3- X from its precursor Aβ 1- X : (i) Pharmacological treatment with a DPP4-specific inhibitor elevated levels of full-length Aβ on the expense of Aβ pE3-40 . (ii) Lentiviral expression of mutant APP cDNA in wild-type mouse brain and pharmacological blocking of DPP4 activity in brain in situ rescued dendritic spine morphology.…”
Section: Generation Of Pyroglutamate Aβmentioning
confidence: 99%
“…In addition, meprin-β can cut between Met-1 and Asp+2 independent from BACE1 [ 20 ]. DPP4 is responsible for the cleavage of the first two N-terminal amino acids of full-length Aβ 1- X generating Aβ 3- X [ 23 , 26 ]. There is one clinical study published that investigated the influence of DPP4 inhibition in patients with dementia [ 52 ].…”
Section: Drug Target Pyroglutamate Aβmentioning
confidence: 99%